Social vulnerability to natural hazards in the Philippines. (September 2022) - Lloyd, Sophie; Gray, Jasmine; Healey, Sarah; Opdyke, Aaron
Abstract: This research sought to measure social vulnerability at the municipal level across the Philippines. Indicators of social vulnerability were identified from literature and relevant census data was collected from the Philippines Statistics Authority (PSA). Principal Component Analysis (PCA) was used to identify underlying components of social vulnerability from this data, and these principal components, as well as an aggregated Social Vulnerability Index (SVI), were mapped at the municipal level. Negative Binomial (NB) regression analysis was then used to validate the SVI using typhoon mortality rates, with results indicating that a one standard deviation (SD) increase in social vulnerability is positively correlated with a 23.4% increase in observed typhoon-related fatalities. The development of a granular and validated SVI can guide researchers seeking to understand how localised vulnerability contributes to disaster risk in the Philippines and assist policymakers in prioritising local government units for disaster risk reduction interventions. Highlights: Identifies components of social vulnerability to natural hazards in the Philippines. Applies spatial clustering to detect hot- and cold-spots of social vulnerability. Validates the developed index using typhoon-related mortality between 2005 and 2015.